Transformação genética em macieira, com o gene bvlI. - Costa, Raquel Rosa da (2011)
he main objective of this work was to introduce the gene bvlI with confirmed potential antifungal of lectin from Bauhinia variegata, Apple Tree (Malus domestica Borkh) cv. Gala, to establish resistance to fungus Coletotrichum gloeosporioides, causing Leaf Spot. Multiplication experiments were performed in vitro regeneration of leaf explant culture and two protocols via Agrobacterium tumefaciens transformation aimed at inserting the gene bvll. The multiplication of shoots the medium that has best results was MS supplemented with 0.1 mg L-1 ANA and 8.3 mg L-1 2iP and, for the regeneration of the best responses were obtained with using MS, supplemented with 30 g L-1 sorbitol, 0.5 mg L-1 ANA and 5 mg L-1 TDZ, reaching a rate of 94.5% of regenerations. As regards the processing protocols, which showed best results was the P1 Protocol, which through analysis of PCR were obtained 15% shoots containing the gene bv/l. However, the expression of BVLI protein was not detected by Dot Blot, indicating the need for further procedure, such as refinement of protein extraction protocol, as well as utilization other techniques of analyses, such as Real Time.